2012
DOI: 10.1262/jrd.11-139n
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Factors That Regulate Ovulation of the Dominant Follicle During the First Follicular Wave Postpartum in High-producing Dairy Cows

Abstract: Abstract. During recent decades, milk production per cow has increased drastically due to improved management, nutrition, and genetic selection; however, the reproductive performance of high-producing dairy cows has been declining. One of the factors responsible for this low reproductive performance is negative energy balance (NEB). NEB affects the onset of first ovulation in early postpartum cows. It is generally accepted that early first ovulation positively relates to the resumption of normal ovarian functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 68 publications
1
43
1
11
Order By: Relevance
“…However, our observations seems not to be in concert with other reports on negative interrelationships between plasma NEFA (Zulu et al, 2002;Kawashima et al, 2007Kawashima et al, , 2012Jackson et al, 2011), insulin (Francisco et al, 2003) and ovarian activity. Here we demonstrate the association between the level of endogenous Zn 2+ (but not other microelements) and bovine ovarian functions: BCS2 cows had higher blood Zn 2+ levels, lower ovarian, follicular and corpora albicantia size in comparison with the BCS3 animals, while granulosa cells isolated from the ovaries of the former released more oestradiol than those obtained from the BCS3 group.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…However, our observations seems not to be in concert with other reports on negative interrelationships between plasma NEFA (Zulu et al, 2002;Kawashima et al, 2007Kawashima et al, , 2012Jackson et al, 2011), insulin (Francisco et al, 2003) and ovarian activity. Here we demonstrate the association between the level of endogenous Zn 2+ (but not other microelements) and bovine ovarian functions: BCS2 cows had higher blood Zn 2+ levels, lower ovarian, follicular and corpora albicantia size in comparison with the BCS3 animals, while granulosa cells isolated from the ovaries of the former released more oestradiol than those obtained from the BCS3 group.…”
Section: Discussioncontrasting
confidence: 76%
“…Cows can be a good model to study the link between reproduction, endocrine system, metabolism, and body condition in females. For example, a negative energy balance in post-partum cows causes rapid body weight loss, increased occurrence of metabolic disorders, changes blood levels of glucose, insulin and IGF-I, which are important factors of ovarian functions (Spicer and Echternkamp, 1995;Zulu et al, 2002;Roche et al, 2009;Jackson et al, 2011;Kawashima et al, 2012;Wathes, 2012). A negative energy balance in such cows may restrict the pulsatile release of gonadotropin-releasing hormone, its downstream targets, gonadotropins (FSH and LH), responsiveness of ovarian tissue to gonadotropins and, therefore, adversely affect normal ovarian follicle development, causing follicle atresia (Butler, 2000;Wathes et al, 2007;Hernandez-Medrano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1). Circulating NEFA concentrations start to increase approximately 2 weeks before calving, peaking at 0-10 days post partum when EB reaches its nadir (Contreras and Sordillo 2011;Kawashima et al 2012). These NEFAs consist mainly of saturated fatty acids, including palmitate (C16:0) and stearate (C18:0), and the monounsaturated fatty acid oleic acid (C18:1n9c; Contreras and Sordillo 2011).…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Non-enzymatic antioxidants include vitamin C (ascorbic acid), vitamin E (a-tocopherol), glutathione and b-carotene (Agarwal et al 2012). b-Carotene acts both as a precursor of vitamin A and independently to enhance host immunological defence mechanisms, but circulating concentrations fall around calving to a minimum at 1-2 weeks post partum (Kawashima et al 2012). Some, but not all, studies have reported that supplementing the diet with bcarotene around this time improves fertility and reduces markers of uterine inflammation (Kaewlamun et al 2011;Kawashima et al 2012).…”
Section: Mitochondria and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation